1995
DOI: 10.1210/endo.136.12.7588313
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific effects of fatty acids on proglucagon-derived peptide secretion in fetal rat intestinal cultures.

Abstract: The ingestion of fats is a potent stimulus for the secretion of the proglucagon-derived peptides (PGDPs), including the insulinotropic peptide glucagon-like peptide-1 from the intestinal L cell. The aim of the study was to characterize the structural requirements for fatty acid-induced secretion of the PGDPs and investigate the cellular mechanisms through which fatty acids mediate PGDP secretion. Fetal rat intestinal cell cultures were incubated with 10-150 microM fatty acids that differed in chain length (14-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 36 publications
4
49
0
Order By: Relevance
“…Similar studies have demonstrated synergistic effects of the monounsaturated fatty acid oleic acid and the enteroendocrine hormone glucose-dependent insulinotropic peptide in the regulation of GLP-1 secretion by GLUTag cells (48,54). In the in vivo setting, GLP-1 is rapidly secreted by L cells upon ingestion of a meal, and by fat and glucose in particular (3)(4)(5), as was also shown in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar studies have demonstrated synergistic effects of the monounsaturated fatty acid oleic acid and the enteroendocrine hormone glucose-dependent insulinotropic peptide in the regulation of GLP-1 secretion by GLUTag cells (48,54). In the in vivo setting, GLP-1 is rapidly secreted by L cells upon ingestion of a meal, and by fat and glucose in particular (3)(4)(5), as was also shown in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that alterations in the fat composition of rodent chow, while maintaining fat content at 5%, do not alter GLP-1 concentrations in the ileum of rats (57), although dietary fat does stimulate GLP-1 release from the intestinal L cell (3,37,40,54). The mechanism(s) by which fat enhances the synthesis and secretion of GLP-1 remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After a mixed meal, the plasma GLP-1 increase has also been shown to be more pronounced with the presence of olive oil than palm oil or butter in healthy humans [39]. Also, in vitro, oleic acid is a stronger stimulator of GLP-1 secretion than saturated fatty acids [52]. The marked increase in GLP-1 at basal glucose concentrations coincided with only a very small increase in plasma insulin concentrations for the three fat tests compared to the control visit.…”
Section: Discussionmentioning
confidence: 99%
“…A study in diabetic mice showed that a high-MUFA diet with a controlled caloric intake could ameliorate impaired glucose tolerance [14]. The mechanism of glucose-lowering action by MUFAs is proposed to be through the reversal of decreased activity of glucokinase, a key enzyme in the catabolism of glucose [15], and through the activation of glucagon-like peptide-1 secretion [16,17], which stimulates glucose-dependent insulin secretion and inhibits food intake.…”
mentioning
confidence: 99%